Charcot Neuroarthropathy in Patients with Diabetes: Assessment of Outcomes in 256 Consecutive Patients. Issue 1 (19th August 2016) - Vaudreuil, Nicholas J.; Fourman, Mitchell S.; Sadoskas, David; Wukich, Dane K.
Category: Diabetes Introduction/Purpose: Charcot neuroarthropathy (CN) has been associated with premature mortality, increased morbidity and reduced health related quality of life. The primary goal of treatment in patients with CN, whether surgical or non-surgical, is to achieve successful limb salvage. Traditionally, the quality of medical evidence guiding treatment has largely been based on expert opinion and uncontrolled case series. A systematic review (FAI 2012) reported that the mean and median number of patients reported in surgical studies of CN was 27 and 14 respectively. This retrospective study was performed to assess the outcomes of a consecutive series of diabetic patients with CN from a single surgeon academic practice. The primary aim was compare the major lower extremity rate (LEA) in patients with and without a preoperative ulcer Methods: This series was comprised of 256 diabetic patients with a mean age of 58.4 years (±10.1). The majority of patients were males (57%), had type 2 DM (78.5%) and used insulin (70.4%). The anatomic areas of CN involvement were midfoot (69.1%), ankle (25.1%), hindfoot (4.7%) and forefoot (0.1%). The majority of patients presented during Eichenholtz stage 3 (61%) followed by stage 1(27%) and stage 2 (12%). At the time of presentation, 144 patients (56%) had a foot ulcer and 58% of ulcer patients (N=84) had either a soft tissue infection or osteomyelitis. When comparing CN patients with and without ulcers, there were no significant differences between the two groups with regard to age, duration of DM, BMI, insulin use, serum glucose, Hbg A1C, serum creatinine, need for dialysis or PAD. Patients with foot ulcers were significantly more likely to be males and have lower levels of hemoglobin and albumin. Results: 75% of patients underwent some type of surgery and 25% were successfully managed without surgery. Major LEA was performed in 39 of 256 patients (15.2%). Three LEA (2.7%) were performed in patients (N=112) who did not have a preoperative ulcer compared to 36 LEA (25%) in patients (N=144) with ulcers (p < 0.0001). These 3 amputations occurred after reconstructive surgery in patients with PAD. Variables associated with major LEA included the presence of a preoperative ulcer [OR 12.1(95% CI 3.6-40.5), < 0.0001], preoperative infection [OR 4.5 (95% CI 2.1-9.8), < 0.0001] and male gender [OR 4.1(95% CI 1.7-9.7), 0.0007]. PAD [OR 1.3 (95% CI 0.6-2.7), 0.48] and dialysis [OR 1.3(0.4-3.6), 0.69] were not significantly associated with LEA. Thirty-seven of 256 patients (14.8%) died during the follow up period Conclusion: This study demonstrates that once an ulcer develops in patients with CN, the need for surgery, complications of surgery (i.e. surgical site infections) and risk of LEA increases significantly. Early treatment (non-surgical or surgical) should strive to prevent ulcer formation. Approximately one in six patients died during the follow up period, indicating that CN is likely a surrogate marker for cardiovascular and renal health. A major limitation of this study is that patients in this series were from an academic practice that receives tertiary referrals. Consequently, the relatively high rates of surgery and amputation may be due to selection bias.